2014
DOI: 10.1017/s1368980014001049
|View full text |Cite
|
Sign up to set email alerts
|

A profile of New Zealand ‘Asian’ participants of the 2008/09 Adult National Nutrition Survey: focus on dietary habits, nutrient intakes and health outcomes

Abstract: Objective: To investigate similarities and differences in dietary habits, nutrient intakes and health outcomes of South Asians (SA) and East and South-East Asians (ESEA) and the New Zealand European and Other (NZEO) group, and to examine differences within 'Asian' subgroups according to duration of residence. Design: Nutrient intake data from 24 h diet recalls and data from the dietary habits questionnaire, anthropometry and biochemical analyses from the cross-sectional 2008/09 Adult National Nutrition Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Low intakes of animal-source foods, low socioeconomic status, and a lower prevalence of supplement use have been suggested as predictors of B 12 deficiency in South Asians (66)(67)(68) . No dietary or demographic data were available in the present retrospective study to determine predictors of the reported differences in B 12 status.…”
Section: Discussionmentioning
confidence: 99%
“…Low intakes of animal-source foods, low socioeconomic status, and a lower prevalence of supplement use have been suggested as predictors of B 12 deficiency in South Asians (66)(67)(68) . No dietary or demographic data were available in the present retrospective study to determine predictors of the reported differences in B 12 status.…”
Section: Discussionmentioning
confidence: 99%
“…Similar downward trends in bread consumption have occurred in the UK and the decline has been attributed to an increased perception of bread as ‘fattening’, the fad to reduce carbohydrate intake, avoidance due to perceived wheat or gluten intolerance or allergies, and increases in the relative price of bread ( 24 ) . In NZ, those of South Asian, East Asian and South-East Asian ethnicities are less likely than NZ Europeans to report consuming bread ( 25 ) . The proportion of these ethnicities is increasing in NZ.…”
Section: Discussionmentioning
confidence: 99%
“…Those reporting consuming alcohol declined between the 1997 and 2008/09 surveys among females aged [19][20][21][22][23][24][25][26][27][28][29][30] years (−11·7 %, P = 0·006) and males aged 31-50 years (−8·7 %, P = 0·023), but the percentage reporting water as a beverage increased for males and females (P < 0·001).…”
Section: Trends In Percentage Reporting Food Groupsmentioning
confidence: 99%
“…Globally, the consumption of rice, which currently provides the majority of daily energy intake and carbohydrate for at least half of the world’s population [1], has been increasing. Since the Joint FAO/WHO Expert Consultation on Carbohydrates in Human Nutrition in April 1997 [2], there has been increased understanding of the diverse physiological roles that carbohydrates have on the rate and extent of digestion in the gut and the relationship between dietary carbohydrates and various non-communicable diseases, including hyperglycaemia, insulin resistance, obesity, metabolic syndrome and type 2 diabetes [3].…”
Section: Introductionmentioning
confidence: 99%